Rereading the Story of Saba’: A Contextual Exploration of Qur’anic Perspectives on Prosperity, Ingratitude, and Ecological Collapse - Akmal Rizki Gunawan Hsb; Nur Najmi Anggraeni (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2024)
This article offers a thematic and contextual rereading of Qs. Saba’ (34:15), a verse that narrates the prosperity and downfall of the ancient Sabaean civilization. Through this verse, the Qur’an articulates a profound ethical vision in which true prosperity emerges from the harmonious integration of spiritual consciousness, social justice, and ecological responsibility. Drawing on classical and contemporary tafsir, this study examines how diverse exegetical traditions interpret key elements of the verse, from historical narratives and theological reflections to socio-environmental concerns. The analysis indicates that the ingratitude and mismanagement of divine blessings exhibited by the Sabaean people function as a historical cautionary tale and a timeless warning concerning the moral and ecological consequences of human negligence. By situating this Qur’anic episode within the context of present-day global challenges, such as environmental degradation, resource exploitation, and widening social inequality, this study argues that the Qur’an offers an enduring ethical framework for reimagining the foundations of sustainable development. In doing so, it contributes to broader discussions on how scriptural traditions can inform contemporary ecological and moral thought.